Fallopian tube prolapses through uterine rent: a rare complication following dilation and curettage - Kumari, Pushplata; Prabathan, Mapitha Venketasamy; Kharsyntiew, Elza Rebecca (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Fallopian tube prolapse (FTP) presents with symptoms of pelvic pain and vaginal discharge and has been reported as a rare complication after hysterectomy without salpingectomy. On other hand, uterine perforation is common complication reported with dilation and curettage (D&C). Authors reported an unusual case of fallopian tube prolapse through the uterine rent as an unrecognised uterine perforation.